Peran Alokasi Dana Desa dan Pendapatan Asli Desa dalam Mendorong Belanja Desa : Bukti Empiris Dari Desa Lompotoo - Amelia Yope; Frahmawati Bumulo; Sudirman Sudirman; Radia Hafid; Rierind Koniyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to measure the Influence of Village Fund Allocation and Village Original Income on Village Expenditure in Lompotoo Village, Suwawa Tengah District, Bone Bolango Regency. This study uses a quantitative approach with a survey method and multiple linear regression techniques. All samples in this study were 30 people taken from village officials, BPD, BUMDes and the Community in Lompotoo Village, Suwawa Tengah District, Bone Bolango Regency. The results of the study indicate that the allocation of Village Funds and Village Original Income of this study indicate that the allocation of village funds and village original income have a simultaneous effect on village expenditure in Lompotoo Village, Suwawa Tengah District, Bone Bolango Regency. The contribution of the allocation of village funds and village original income to explain village expenditure is 0.467, which means that the allocation of village funds and village original income contribute 46.7% to village expenditure. The hypothesis can be stated as simultaneously accepted, where the allocation of village funds and village original income together have a positive and significant effect on village expenditure. The less than optimal contribution shows that there are still many other variables that influence village spending in Lompotoo Village, Suwawa Tengah District, Bone Bolango Regency, besides village fund allocation and original village income.